Integrated Strategies Toward the Capture and Electrochemical Conversion of Low‐Concentration Carbon Dioxide - Zhenyi Yang; Xingqiu Li; Xianglong Cui; Zhen Zheng; Penglun Zheng; Yu Zhang (Exploration)
ABSTRACT Electrochemical reduction of carbon dioxide (CO2) has been considered a promising route to reduce net carbon emissions and thus mitigate global warming issues. In practice, it mainly involves two processes including the CO2 capture and subsequent electrochemical conversion. From the perfective of feasible and economic benefits, it is of practical significance to develop integrated CO2 capture and conversion systems in an efficient way. However, a majority of studies have been currently focusing on the independent process, and the development of integrated strategies is still in the initial stage. This review mainly covers the recent progress on the integrated technologies of CO2 capture and electrochemical conversion, including the integration strategies, mechanisms, and corresponding issues. The advantages and disadvantages of those strategies are particularly discussed, aiming to identify the viable routes for future applications. To conclude, the challenges and prospects in terms of the research direction in this field are provided, with the hope of promoting practical CO2 utilization from the fundamental aspects.